Income Inequality, Poverty, and Inclusive Economic Development: Evidence from Gorontalo Province, Indonesia - Masia, Israwanto; Saleh, Sri Endang; Mopangga, Herwin (Journal of International Conference Proceedings, 2025)
Income distribution (Gini ratio) plays an important role in determining the level of public welfare and the quality of inclusive economic development. High income inequality can worsen poverty conditions and hinder the creation of equitable development. This study aims to analyze the effect of income distribution on inclusive economic development in Gorontalo Province by considering poverty as an intervening variable. The method used is path analysis with secondary data from the Gorontalo Province BPS during 2011–2024. The results show that income inequality has a positive and significant effect on poverty and a negative and significant effect on inclusive economic development. Poverty also has a negative impact on inclusive economic development and serves as a significant intervening variable. These findings imply that reducing inequality and poverty is crucial in promoting sustainable inclusive economic development in Gorontalo Province.